Artemis Fowl and the time paradox - Colfer, Eoin. (London : Puffin Books, 2011)
Artemis's fairy friends help him travel back in time to find a cure for his mother's rare disease which can only be cured by the brain fluid of now-extinct African lemurs, and is shocked to discover that it was actually his younger self who was responsible for bringing about the animal's extinction.
5.8.
5-8.
Keywords: Fairies -- Juvenile fiction; Fowl, Artemis (Fictitious character) -- Juvenile fiction; Magic -- Juvenile fiction; Time travel -- Juvenile fiction; Adventure and adventurers -- Fiction; Fairies -- Fiction; Fowl, Artemis (Fictitious character) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Adventure fiction; Fairies -- Fiction; Fowl, Artemis (Fictional character) -- Fiction; Magic -- Fiction; Time travel -- Fiction